State crime, women and gender - Collins, Victoria E. (Routledge studies in crime and society, 2016)
1. State crime, women and gender : an introduction -- 2. Definitional issues and an introduction to relevant concepts -- 3. The feminist perspective and theories of gender-based violence -- 4. War, violence and women : direct forms of state-perpetrated violence against women -- 5. Peace for whom? Indirect forms of state-perpetrated violence against women -- 6. Female criminality and state violence -- 7. State power consumed, replicated and reinforced -- 8. Women, resistance and the state -- 9. Voices of victimization : access to justice for female victims of state-perpetrated violence -- 10. Administering justice : women working in the international criminal justice system -- 11. Concluding thoughts.